ReSharper essentials : make your Microsoft Visual studio work smarter with ReSharper - Gąsior, Łukasz (Community experience distilled., 2014)
A practical, hands-on guide that will help you to unleash the power of ReSharper to write better quality code. If you are a developer who is working with Visual Studio and are looking to make your work more efficient, this book is for you. It is most useful for new ReSharper users but those who are currently using it will also find many useful tips and references updated to the latest version (8.1). Prior knowledge of Visual Studio is a must.